2020
DOI: 10.1017/njg.2020.6
|View full text |Cite
|
Sign up to set email alerts
|

Fracture characteristics of Lower Carboniferous carbonates in northern Belgium based on FMI log analyses

Abstract: Recently drilled geothermal boreholes in Mol, northern Belgium, provide new information on the Lower Carboniferous carbonates in the Campine–Brabant Basin. Because of low primary porosity, fractures in these limestones and dolostones are of major importance for reservoir permeability. The Fullbore Formation MicroImager (FMI) log of the MOL-GT-01 borehole enabled interpretation of bed boundaries and fractures in the subsurface. Relationships between the frequency of these fractures and bed thickness, lithology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…These results are similar to the subsurface Lower Carboniferous carbonates in Mol, northern Belgium. FMI log analyses of the MOL-GT-01 and -03 have shown that no clear correlation is present 27 between bed thickness and fracture frequency in these boreholes (Van der Voet et al, 2020a, 2020b.…”
Section: Effects Of Bed Thickness On Fracture Networkmentioning
confidence: 87%
See 1 more Smart Citation
“…These results are similar to the subsurface Lower Carboniferous carbonates in Mol, northern Belgium. FMI log analyses of the MOL-GT-01 and -03 have shown that no clear correlation is present 27 between bed thickness and fracture frequency in these boreholes (Van der Voet et al, 2020a, 2020b.…”
Section: Effects Of Bed Thickness On Fracture Networkmentioning
confidence: 87%
“…Fracture characteristics of these carbonates were studied based on borehole cores (Van der Voet et al, 2020c) as well as from image logs ( Van der Voet et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%